WINDOWS OF OPPORTUNITY. (Architects' Journal, 2006)
The article presents information about new software applications launched by Apple Computer Inc. For a month now, everyone has known that it is possible to run Windows on Intel-powered Macs. Therefore, Apple has introduced a newly downloadable application, Boot Camp to make it easy for users to run Windows on Intel-powered Macs. Apple's shares jumped by nearly 7 per cent on the announcement of Boot Camp. Two days later, Parallels brought out a beta of its Workstation, which runs Windows inside Mac operating system X.